Boreholes on three bivalve species found on the sand beach at Sagot Cape, Baengnyeongdo, Korea - Kong, Dal-Yong; Lee, Mi-Hee; Park, Chan Hong; Lee, Seong-Joo (Journal of Asia-Pacific biodiversity, 2017)
Circular to subcircular boreholes were found on the surfaces of three different bivalve shells (Mactra chinensis, Felaniella usta, and Nuttallia japonica) that were pushed onto the sand beach at Sagot Cape, Baengnyeongdo, Korea. The boreholes are characterized by beveled holes that are parabolic in cross section. The boreholes are classified into the ichnospecies Oichnus paraboloides, probably drilled by a naticid gastropod Glossaulax didyma didyma living in the Baengnyeong tidal flat. In the case of Mactrashells, boreholes are observed more or less evenly on left and right valves, and 96% of boreholes are located on the umbo. This may suggest that the life position of the Baengnyeong bivalves did not dictate the preference of G. didyma didyma in the Baengnyeong tidal flat ecosystem. The clustered distribution of the boreholes in the umbo area indicates a strong site selectivity for boreholes that is quite a common phenomenon in many naticid gastropods.